Analisis Kemampuan Teknik Dasar Pemain Sepak Bola - Hasani, Birrul; Arifin, Ramadhan; Fauzan, Lazuardy Akbar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the level of mastery of basic techniques of GSI Banjarbaru players in playing soccer. The method used is qualitative descriptive research. The results of the study indicate that the passing technique is included in the category of